Cannabinoid CB1 receptor mediates METH-induced electrophysiological and morphological alterations in cerebellum Purkinje cells. (June 2021) - Ramshini, Effat; Sheykhzade, Majid; Dabiri, Shahriar; Shabani, Mohammad
Our previous studies on cannabinoid type1 receptor (CB1R) activation on Methamphetamine (METH)-induced neurodegeneration and locomotion impairments in male rats suggest an interaction between CB1Rs and METH. However, the role of these receptors in METH-neurotoxicity has not been fully identified. Therefore, the purpose of the present study is to investigate the involvement of CB1Rs in these effects. We conducted an electrophysiological study to evaluate functional interactions between METH and CB1Rs using whole-cell patch current clamp recording. Furthermore, we designed the Nissl staining protocol to assess the effect of METH on the basic cerebellar Purkinje cell structure. Our findings revealed that METH significantly increased the action potential half-width, spontaneous interspike intervals, first spike latency, and decreased the rebound action potential and spontaneous firing frequency. Using CB1R agonist and antagonist, our results showed a significant interaction with some of the electrophysiological alterations induced by METH. Further, Nissl staining revealed that the exposure to the combination of METH and SR141716A resulted in the necrotic cell death. Results of the current study raises the possibility that METH consumption profoundly affect the intrinsic membrane properties of cerebellar Purkinje neurons and cannabinoid system manipulations may counteract some of these effects. In summary, our findings provide further insights into the modulatory role of the endocannabinoid system in METH-induced neurologic changes, which can be used in the development of potential therapeutic interventions for METH dependence.